Potential of oil palm empty fruit bunch resources in nanocellulose hydrogel production for versatile applications: a review - Mohammad Padzil, Farah Nadia; Lee, Seng Hua; Mohamed @ Asa'ari, Ainun Zuriyati; Lee, Ching Hao; Abdullah, Luqman Chuah (MDPI, 2020)
Oil palm empty fruit bunch (OPEFB) is considered the cheapest natural fiber with good properties and exists abundantly in Malaysia. It has great potential as an alternative main raw material to substitute woody plants. On the other hand, the well-known polymeric hydrogel has gathered a lot of interest due to its three-dimensional (3D) cross-linked network with high porosity. However, some issues regarding its performance like poor interfacial connectivity and mechanical strength have been raised, hence nanocellulose has been introduced. In this review, the plantation of oil palm in Malaysia is discussed to show the potential of OPEFB as a nanocellulose material in hydrogel production. Nanocellulose can be categorized into three nano-structured celluloses, which differ in the processing method. The most popular nanocellulose hydrogel processing methods are included in this review. The 3D printing method is taking the lead in current hydrogel production due to its high complexity and the need for hygiene products. Some of the latest advanced applications are discussed to show the high commercialization potential of nanocellulose hydrogel products. The authors also considered the challenges and future direction of nanocellulose hydrogel. OPEFB has met the requirements of the marketplace and product value chains as nanocellulose raw materials in hydrogel applications.